2020
DOI: 10.1089/whr.2020.0035
|View full text |Cite
|
Sign up to set email alerts
|

Specific Nutrient Intake Via Diet and/or Supplementation in Relation to Female Stress: A Cross-Sectional Study

Abstract: Background: Women are negatively impacted by psychological stress and despite the prolific use of dietary supplements to manage stress there is little evidence to support their use for such. This study examined the relationship between intake of specific nutrients through diet and/or dietary supplementation and level of perceived stress. Method: In this cross-sectional study of adult Australian women (n = 74), perceived stress was measured using the Perceived Stress Scale, dietary intake was assessed using a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The objective of this qualitative study was to examine the lived experience of stress among women and their use of diet and/or DSs to manage stress. A cross‐sectional study that examined the relationship between psychological stress and dietary supplement intake found no significant relationship between any specific nutrient and stress among the sample of women, and helped inform the research questions in this study (McCabe, Bednarz, Lockwood, & Barker, 2020).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The objective of this qualitative study was to examine the lived experience of stress among women and their use of diet and/or DSs to manage stress. A cross‐sectional study that examined the relationship between psychological stress and dietary supplement intake found no significant relationship between any specific nutrient and stress among the sample of women, and helped inform the research questions in this study (McCabe, Bednarz, Lockwood, & Barker, 2020).…”
Section: Introductionmentioning
confidence: 86%
“…A population of 74 women who had participated in a preceding crosssectional survey (McCabe et al, 2020), that examined the relationship between stress and specific nutrients consumed via diet and/or DSs, were invited to take part in this PAR study. Thus, although this was a convenience sample, it was also purposivewe were also selecting from a group of women who had previously acknowledged their lived experience of stress and were therefore able to call upon experience particular to this study.…”
Section: Samplementioning
confidence: 99%
“…Analysis of this school of thought indicates that dietary supplements must contain vitamins, minerals, fiber, amino acids, herbs or other plants or enzymes. Moreover, it has revealed that certain supplements can help to ensure that the individual receives enough vital substances that the body needs to function, or they help to reduce the risk of disease, although it emphasizes that supplements should not completely replace foods that are necessary for a healthy diet, as indicated by the Food and Drug Administration (FDA), federal agency of the Department of Health and Human Services (HHS) of the United States [101,102].…”
Section: Analysis Of Abstract: Detection Of Current Lines Of Researchmentioning
confidence: 99%
“…A previous study by Leng et al suggested that a higher level of stress can be considered harmful and has a certain degree of negative impact on a person’s health [ 3 ]. It impairs emotional, physical, cognitive, and social functioning [ 4 ] and puts people at increased risk of stress-related health problems, especially depression [ 5 ]. Bremner et al, reviewed the associations between diet, stress, and stress-related disorders.…”
Section: Introductionmentioning
confidence: 99%